2014
DOI: 10.1111/hpb.12281
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and pancreatic resection in patients with end-stage renal disease: a propensity analysis

Abstract: Hepatic and pancreatic resections can be performed safely in selected patients with ESRD. These patients may have an increased risk for the development of postoperative sepsis. Further study is needed to characterize modifiable risk factors that impact outcomes in patients with ESRD who require hepatic or pancreatic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…It can be also hypothesized that severe jaundice alters immunologic function thus increasing the rate of infectious complications (35). An impaired renal function before pancreatic surgery results in an increased risk of postoperative severe sepsis or septic shock (33,34). Both severe jaundice and impaired renal function seem to have a cumulative negative effect of the early postoperative course, as suggested by the result of multivariate analysis in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…It can be also hypothesized that severe jaundice alters immunologic function thus increasing the rate of infectious complications (35). An impaired renal function before pancreatic surgery results in an increased risk of postoperative severe sepsis or septic shock (33,34). Both severe jaundice and impaired renal function seem to have a cumulative negative effect of the early postoperative course, as suggested by the result of multivariate analysis in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…Twenty-three studies extracted information from existing data registries while the remaining extracted information from re-examined health records. Thirty-three studies were reported from North America [ 2 , 15 17 , 21 – 24 , 27 – 29 , 31 , 33 37 , 40 , 42 , 44 46 , 49 , 51 56 , 58 , 60 , 62 ], ten from Asia [ 18 – 20 , 26 , 30 , 38 , 39 , 43 , 47 , 48 , 50 , 59 ] and four from Europe [ 14 , 32 , 41 , 57 ]. Thirty-four studies were published after 2010 [ 2 , 14 , 16 , 22 – 24 , 27 – 31 , 33 , 34 , 36 50 , 53 56 , 58 60 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…All 49 studies reported age and gender, but comorbidities were less consistently described, with 37 (76%) studies reporting the prevalence of diabetes mellitus [ 2 , 14 – 19 , 21 , 23 30 , 33 , 34 , 36 41 , 43 , 46 , 47 , 49 54 , 60 , 62 ], 32 (65%) reporting ischemic heart disease (IHD) [ 2 , 14 21 , 23 , 25 , 27 – 30 , 34 , 36 41 , 46 49 , 51 54 , 60 , 62 ], 20 (41%) reporting smoking status [ 17 , 19 , 23 , 25 , 26 , 28 , 29 , 33 35 , 37 , 38 , 46 , 49 52 , 54 , 60 – 62 ], and 14 (29%) studies reporting all three comorbidities [ 19 , 25 , 28 , 29 , 33 , 37 , 46 , 49 , 51 , 52 , 54 , 60 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies defined normal kidney function by serum creatinine. Non-emergent cardiac surgery was the most commonly reported type of surgery (15 studies, 31%), [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] followed by general surgery (12 studies, 25%), [4,[35][36][37][38][39][40][41][42][43][44][45] vascular surgery (9 studies, 18%), [41,[46][47][48][49][50][51][52][53] orthopaedic surgery (9 studies,18%) [54][55][56][57][58][59][60][61] and urologic/gynaecologic surgery (4 studies, 8%)(62-65). Twenty-two of the 49 studies assessed a single surgical procedure, [24-27, 29, 31-34, 39, 41, PLOS ONE https://doi.org/10.1371/journal.pone.0234402.g001 Thirty six studies did not report dialysis modality, eleven studies specifically examined haemodialysis patients only,…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…[20, 39, 56, 62] Thirty four studies were published after 2010. [4, 20, 22, 29-31, 34-38, 40, 41, 43-46, 50-61, 63-67] All 49 studies reported age and gender, but comorbidities were less consistently described, with 37 (76%) studies reporting the prevalence of diabetes mellitus, [4, 20-25, 27, 28, 30-37, 40, 41, 43, 45-56, 58, 61, 65-67] 31 (63%) reporting ischaemic heart disease(IHD), [4, 20-28, 30, 32, 34-37, 41, 43, 45, 47-50, 52-56, 61, 65, 67] 21 (43%) reporting smoking status,[23, 25, 30, 32-36, 40-42, 46-49, 51, 53, 67] and 15 studies (31%) reporting all three comorbidities [32,35,36,45,47,49,52,61,65,[68][69][70][71][72][73].…”
mentioning
confidence: 99%